The Implementation of Parenting Styles within Families on Adolescent Development - Christina Anugrahini; Pius Almindu Leki Berek; Sri Lestari; Maria Fatimah Wilhelmina Abuk Fouk; Sefrina Maria Seuk Asa; Yusfina Modesta Rua (Indonesian Journal of Global Health Research, 2025)
Adolescence is a crucial transitional phase in individual development, characterized by physical, emotional, cognitive, and social changes. During this period, adolescents begin to form their self-identity, seek independence, and often experience conflicts with authority figures, particularly with parents. Parenting style refers to the approach or pattern used by parents to educate, guide, and shape their children’s behavior and character. This study aims to explore the implementation of parenting styles within families toward adolescent development at St. Angela Senior High School, Atambua, East Nusa Tenggara. This research employed a qualitative phenomenological design using in-depth interviews. The participants consisted of 10 individuals: five parents (either father or mother) who have adolescent children aged 13–18 years, and five adolescent participants who are raised by these parents. The study identified nine emerging themes: (1) Parental perspectives on raising adolescents; (2) Core values and principles in parenting; (3) Adolescents’ freedom in decision-making; (4) Conflict management and handling differences of opinion; (5) The nature of parent–child relationships; (6) Adolescents’ perceptions of parental understanding of their needs; (7) Perceptions of parental trust and autonomy; (8) Parental responses to children’s mistakes; and (9) Adolescents’ perceptions of parenting styles.Parenting styles-authoritarian, authoritative  (democratic), and permissive-serve as the foundation for how parents nurture their adolescent children. Among these, the authoritative style is found to be the most adaptive and psychologically healthy for adolescent development.